Processing, microstructure and piezoelectric properties of Li-doped BCZT ceramics. Issue 3 (1st February 2023) - Liu, Chen; Zou, Ji; Wang, Xinwei; Zhang, Tailin; Ye, Guoyang; Button, Tim; Binner, Jon
Abstract: Li2 CO3 is a promising additive to reduce the sintering temperature for (Ba0.85 Ca0.15 ) (Zr0.1 Ti0.9 )O3 (BCZT) ceramics, however, the solubility of Li2 CO3 in water and the high volatility of Li2 O at elevated temperatures make the processing and densification of BCZT-Li2 CO3 ceramics (known as BCZT-L) challenging. In our work, an optimized processing route was developed to obtain dense and flat BCZT-L ceramics made with 0–10 mol% of Li2 CO3 and involving sintering at 1300 °C–1400 °C. The chemical and structural evolution of BCZT-L ceramics during sintering with and without a BCZT powder bed are comprehensively documented and the distribution of Li in the matrix has been observed through TOF-SIMS to explain the effects of Li doping on the piezoelectric properties. The d 33 and k p of BCZT-L initially increased with Li content, but then decreased with excess Li. The decreased d 33 and k p with excess Li is associated with Li aggregation in the BCZT matrix.